Empowerment of Productive Economic Business for The Poor in Serang City - Iis Ismawati; Helmi Yazid (EQUATOR SINAR AKADEMIA, 2022)
Community service is how to empower the poor in urban areas through productive economic efforts, problem identification The number of poor people tends to increase, the existing business opportunities are relatively limited, productive economic businesses are not optimal and market access is limited for business groups. The purpose of the activity is to foster an entrepreneurial spirit for the poor through the formation of joint business groups, to empower the potential of the poor in increasing family income through increasing productive economic enterprises. The process of community empowerment in the village begins with the formation stage, then implementation and the last is the stage of handing over assistance. problems related to the factors that influence the dynamics of joint business groups in Banjar Village, increasing productive economic efforts of joint business groups, more directed to chess efforts to improve product quality, production cost efficiency, marketing expansion and business scale improvement.